WIRELESS SENSOR SYSTEM UNTUK MONITORING KONSENTRASI DEBU MENGGUNAKAN ALGORITMA RULE BASED - Agus Sulistiyo; Suryono Suryono (Youngster Physics Journal, 2016)
Air is the source of life required of all living beings. The level of air pollution is increasing as the development of the industrial sector. Monitoring of air pollution levels are needed to determine the air quality at a given location. One indicator of air quality is the concentration of dust, so we need a system of monitoring the concentration of dust in the air that can be monitored in realtime. The method used for system monitoring dust concentrations in this study using telemetry system utilizing a WiFi network. The use of telemetry systems have been more efficient that measurement can be done remotely and measurements can be realtime. Dust concentration measurement using DSM501A dust sensor that produces an output PWM (Pulse Width Modulation). These sensors are connected with the minimum system microcontroller. The microcontroller used is ATmega8535 where the microcontroller has features USART (Universal Synchronous and Asynchronous serial Receiver and Transmitter) as a serial communication mode. RS-232 protocol is used to connect a serial communication data to the computer Remote Terminal Unit (RTU) that located in the location of data collection. The data obtained is sent to a personal computer (PC) Control Terminal Unit (CTU) in monitoring stations with telemetry systems using WiFi networks and saved in database. The conversion result DSM501A dust sensor readings between the low ratio (%) and the value of dust concentration (mg / m3) has a correlation coefficient R = 0.999. Results of the comparison between the data transmitted and received data has error = 0 so it can be concluded no data is lost or gained.Keywords: air quality, dust sensors, telemetry, serial communication.